2021
DOI: 10.1002/fsn3.2323
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and nutritional profile of maize bran‐enriched flour in relation to its end‐use quality

Abstract: The core objective of current research was determined to nutritional and bioactive profile of maize bran (MB)‐enriched flour in relation to its end‐use product quality. Furthermore, rheological properties of MB‐enriched flour at different levels (5%, 10%, and 15%) were explicated through farinograph and mixograph. Moreover, bread was prepared with the addition of MB‐enriched flour and was characterized for nutritional and textural properties. Results showed that MB‐enriched flour having high water absorption a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 29 publications
1
13
0
Order By: Relevance
“…Except in sorghum, samples with bran and hull had higher fat content than samples without bran and hull. Yadav et al [29] found that increase in wheat bran decrease fat content of samples they assessed, this statement is true of the sorghum sample reported in this study, but Hussain et al [25] reported increase in fat content with increase in maize bran ratio.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…Except in sorghum, samples with bran and hull had higher fat content than samples without bran and hull. Yadav et al [29] found that increase in wheat bran decrease fat content of samples they assessed, this statement is true of the sorghum sample reported in this study, but Hussain et al [25] reported increase in fat content with increase in maize bran ratio.…”
Section: Discussionmentioning
confidence: 49%
“…The low moisture content in samples with bran and hull could be attributed to the presence of the bran and hull. Hussain et al [25] reported a decrease in moisture content in maize bran-wheet composite flour with increase in bran content. Owuno and Achinewhu [26] also reported a decrease in moisture content of fermented maize residue-wheat composite flour.…”
Section: Discussionmentioning
confidence: 99%
“…A wide range of pharmacological properties have also been found associated with pumpkin. Previous studies on pumpkin have proven that not only pulp but peel and seeds of pumpkin also have beneftable nutritional profles so, instead of discarding each fraction of pumpkin should be utilized to develop good quality functional and pharma foods [53,54]. While reviewing the literature about the nutritional profles of pumpkin and developed food products from pumpkins, so many data are present but there are only few research studies about the efect of the addition of pumpkin powders on the rheology and physical characteristics of the developed bakery products, as process efciency and product quality are the bench marks for the development of bakery products.…”
Section: Novelty Behind the Researchmentioning
confidence: 99%
“…Roth et al (2015) found positive effects of particle size of distiller's spent wheat grains on development time and stability, with unground spent grain (particle size below 1250 μm) presenting higher development time and stability than control and spent grain with particle size below 750, 500, and 250 μm. Hussain et al (2021) attributed the positive effect of corn bran on development time to its increased surface area, enhancing water absorption, lowering fiber interference in gluten strength and in bread quality through hydrophilic interactions between fibers and water bonded to proteins and starches, raising interactions among dispersed and hydrated gluten-forming proteins.…”
Section: Effects Of Bsg On Dough Development Time and Stabilitymentioning
confidence: 99%